Combination of nitrogen and organic fertilizers reduce N2O emissions while increasing winter wheat grain yields and quality in China - Jin, Yakang; Chen, Hong; Tang, Xiaoqian; Zhang, Lei; Yan, Jun; Li, Shuangjun; Chen, Ya; Li, Xinwei; Wu, Hongbao; Xiao, Xin (Frontiers in Environmental Science, 2024)
Wheat grain yields, quality, and nitrous oxide (N2O) emissions were controlled through the type and application rate of nitrogen (N) fertilizer. Here, we investigated the optimal management of N fertilization by examining the combined effects of organic and N fertilizers on wheat yields, quality, and N2O emissions. Field trials under six treatments were located on campus farms at Anhui Science and Technology University, including farmer’s common practice (270 kg N ha-1, N270), 2/3 reduction in N270 (90 kg N ha-1, N90), organic fertilizer with equal N270 (OF270), 2/3 reduction in OF270 (OF90), 4/5 reduction OF270 + 1/5 reduction N270 (20% OF270 + 80% N270), and 4/5 reduction OF90 + 1/5 reduction N90 (20% OF90 + 80% N90) were applied to winter wheat. The plots were arranged in a randomized complete block experimental design. The N2O emissions were quantified under different fertilization measures in the peak wheat growing season during sowing, jointing, and grain filling stages, respectively. Compared with N270 and N90 treatments, N2O emissions were significantly decreased by 18.6% and 27.2%, respectively, under 20% OF270 + 80% N270% and 20% OF90 + 80% N90 (p < 0.05). Further, N2O emissions in N270 were increased by 50.8% relative to N90. Wheat yields increased significantly under 20% OF90 + 80% N90 by 27.6% (N270) and 16.4% (N90), and were considerably enhanced under 20% OF270 + 80% N270 by 40.6% (N270) and 12.7% (N90) in contrast to OF270 and N270 (p < 0.05). Compared with N90, the content of wet gluten, protein and starch under 20% OF90 + 80% N90 treatment significantly increased by 7.7%, 13.8% and 7.9%, and enhanced by 7.6%, 4.8%, 8.0% relative to OF90, respectively (p < 0.05). The starch content increased significantly by 2.0%, whereas the settlement value decreased considerably by 2.9% under 20% OF270 + 80% N270 (p < 0.05), and there was no notable difference in the wet gluten and protein contents (p > 0.05). Our findings indicated that organic fertilizer mixed with N fertilizer can effectively reduce N2O emissions, increase both the grain yields and quality in wheat field compared with N fertilizer alone.